2013
DOI: 10.1007/s13181-013-0314-y
|View full text |Cite
|
Sign up to set email alerts
|

2-(4-Iodo-2,5-dimethoxyphenyl)-N-[(2-methoxyphenyl)methyl]ethanamine (25I-NBOMe): Clinical Case with Unique Confirmatory Testing

Abstract: Introduction 2C designer drugs have been in use since the 1970s, but new drugs continue to develop from substitutions to the base phenethylamine structure. This creates new clinical profiles and difficulty with laboratory confirmation. 2-(4-Iodo-2,5-dimethoxyphenyl)-N-[(2-methoxyphenyl)methyl]ethanamine (25I-NBOMe) is a relatively new 2C drug that is more potent than structural 2C analogs; exposure reports are rare. Testing for 2C drugs is developing; specific testing for new analogs such as 25I-NBOMe is a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 7 publications
1
68
0
4
Order By: Relevance
“…Only a few pharmacologic studies on humans have been conducted on these drugs. Reports of adverse effects after ingestion began to appear in the scientific literature in 2013, describing prominent neuropsychiatric effects and instability 6,[10][11][12][13][14][15][16] . In severe cases death can occur even after ingesting a single dose 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few pharmacologic studies on humans have been conducted on these drugs. Reports of adverse effects after ingestion began to appear in the scientific literature in 2013, describing prominent neuropsychiatric effects and instability 6,[10][11][12][13][14][15][16] . In severe cases death can occur even after ingesting a single dose 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Presently, NBOMe are not a part of routine drugs-of-abuse screening and there are no rapid color screening tests or pointof-care devices that can quickly detect them 11 . Just a few commercial reference laboratories offer a qualitative test to identify those compounds 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It can present with sympathomimetic and serotonergic symptoms [1][2][3]. Reported adverse effects include multi-organ failure, hypertension, tachycardia, aggression, hallucinations, seizures, hyperthermia, acidosis, and acute kidney injury [1,2,4]. Among the 12 reported cases in the medical literature, three have died [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…6 Few scientific studies have shown the toxicological effects caused by the ingestion of NBOMe series substances. [6][7][8] Research has been primarily focused on human post mortem detection 9,10 and in some cases, in the field of clinical pharmacology; [11][12][13] in Colombia, the only study that has been reported was performed in 2010 and focused on the analysis of substances commercialized in the city of Bogotá under the name synthetic drugs. 14 Colombian law, unlike that of other countries, 15 does not regulate the production and distribution of derivatives of the NBOMe series because these derivatives are not officially included in the lists for control and supervision of psychotropic substances provided by the United Nations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent research shows that these substances can be used as adulterants of traditional drugs. [3][4][5][6][7][8][9][10][11][12][13][14][15] The aim of the present study is to propose a method for the qualitative analysis of substances of the NBOMe series found in blotter papers using gas chromatography coupled to a selective mass ion trap detector (GC-MS IT). This analytical method was tested using samples collected in the city of Bogotá with the aim of providing evidence regarding the marketing of new psychoactive substances.…”
Section: Introductionmentioning
confidence: 99%